Typology of Community Participation in the Development of the Likupang Special Economic Zone (SEZ) through the Smart Environment Tourism Approach - Joune Ganda; Lady Grace Jane Giroth; Bobby Hamenda; Felly Ferol Warouw (Journal of International Conference Proceedings (JICP), 2021)
Regency, North Sulawesi Province which is also included in the government's strategic program for the development of tourism potential, known as Super Priority Destinations or Likupang Special Economic Zones. Tourism is one of the pillars of sustainable tourism that has contributed significantly to development. Tourism should be planned according to the criteria of a sustainable development standard with a smart environmental approach. The achievement of the smart environment criteria is determined by the role of community participation. This study aims to identify community participation in tourism development in Super Priority Destinations, North Minahasa Regency, North Sulawesi Province. The research location was conducted in the Likupang tourism development area. The research method used is descriptive quantitative. The results of the research on identifying the typology of community participation in the development of the Likupang Super Priority Destination show a stratified order of typology of community participation starting from the stages of information, consultation, cooperation, control, and adaptation. The results of the identification of the typology of community participation that meet the five criteria become the basis for determining the position of the level of community participation. The participation typology found is used as the basis for determining policy scenarios for the development of Likupang Super Priority Destinations. The policy scenario that must be carried out in each stage of the development of the tourist area is determined by public opinion. This scenario can be a typology to guide the knowledge transfer of local communities, empowering them to take advantage of their participatory role for the improvement of sustainable ecotourism development. Keywords: Typology, Community, Participation, Tourism, Smart, Environment, Likupang.